Stress-strain behavior of sand at high strain rates - Omidvar, Mehdi; Iskander, Magued; Bless, Stephan (International journal of impact engineering, 2012)
A review of the response of sand under high strain rate (HSR) loading is presented. The response observed in HSR uniaxial compression tests, split-hopkinson pressure bar (SHPB) tests, and triaxial tests is investigated. Previous monotonic HSR tests have been reviewed, summarized, and combined in order to illustrate the effects of HSR loading on the confined modulus, stress-strain response, and shear strength of sand. The effects of strain rate, initial void ratio, confining pressure, saturation, shape and size of grains, as well as grain mineralogy on the response of sand to HSR loading are also discussed. Issues related to inertial effects that may affect HSR response are explored. A brief summary of the response of sand to shock loading is also presented. The review provides a comprehensive understanding of the important aspects of HSR response of sand, in support of the growing interest in the behavior of sand subject to rapid loading conditions. ► High strain rate (HSR) behavior of sand is explored. ► Available HSR triaxial, split-hopkinson, uniaxial and shock test data is reviewed. ► Effect of HSR loading on stress-strain behavior and modulus is summarized. ► Trends of high strain rate behavior are identified.